Spatial Analysis of Pneumonia Distribution in Children Under Five in West Java: Relationships with Individual and Environmental Determinants - Puput Leni Yuliani Suchery; Sutanto Priyo Hastono (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Pneumonia is a major cause of mortality among children under five, especially in developing countries like Indonesia. In 2023, West Java recorded over 18,000 cases, making it one of the provinces with the highest burden. This study analyzes the spatial distribution of pneumonia in children under five across 27 districts/cities in West Java and examines its association with individual and environmental determinants. Data were obtained from the 2023 Indonesia Health Survey (Survei Kesehatan Indonesia or SKI), Statistics Indonesia (Badan Pusat Statistik or BPS), and the West Java Health Office. Descriptive analysis (mean, median, standard deviation) was conducted using SPSS, and geospatial mapping was performed using QGIS. The results revealed notable spatial clusters of pneumonia incidence among children under five in several districts. High-High clusters, indicating areas with high pneumonia rates surrounded by similarly high-risk districts, were prominently observed in regions with elevated prevalence of household tobacco smoking and use of wood fuel for cooking, such as Bogor, Sukabumi, Cianjur, and Garut. Conversely, Low-Low clusters, representing low pneumonia incidence surrounded by similarly low-risk districts, were identified in areas with better population density management and lower tobacco exposure, such as Majalengka, Cirebon, and Kuningan. Significant gaps in basic immunization coverage and exclusive breastfeeding practices were also spatially evident. Districts like Karawang and Purwakarta demonstrated Low-Low clusters for basic immunization, highlighting regional disparities potentially due to limited healthcare accessibility. Likewise, Majalengka and Indramayu showed Low-Low clusters for exclusive breastfeeding practices, signaling inadequate maternal and community support. This spatial epidemiological analysis highlights critical hotspots and underscores the importance of geographically targeted health policies, including intensified immunization campaigns, promotion of exclusive breastfeeding, and tobacco control initiatives, to effectively reduce pneumonia risks among vulnerable children in West Java.